Monitoring Kidney Function Through the Use of Candesartan, Telmisartan or Valsartan Antihypertensive Therapy towards Patients CKD - Selly Septi Fandinata; Rizky Darmawan; Primanitha Ria Utami; Ninik Mas Ulfa (Media Kesehatan Masyarakat Indonesia, 2022)
Chronic Kidney Disease (CKD) lower kidney function caused by an irreversible reduction in normal nephron function. Globally, CKD contributes to the cause of death. Activation of the Renin-Angiotensin-Aldosterone system is involved in the pathogenesis. ARBs have a cardiorenal protective effect. The purpose of this study was to determine the changes in kidney function with the use of Candesartan, Telmisartan or Valsartan antihypertensive therapies in CKD patients. This research method was a prospective observational cohort study looking at changes in kidney function (BUN and Serum Creatinine) at 1 and 6 months of using Antihypertensive Drugs Valsartan, Telmisartan, and Candesartan and tested by statistical analysis. The number of samples in this study was 72 patients which are 24 patients (Candesartan), 27 patients (Telmisartan), and 21 patients (Valsartan). The results showed that the Candesartan group experienced a decrease in average BUN of 0.13±0.85 mg/dl and serum creatinine of 0.004±0.09 mg/dl with independent t-test p=0.479 (p>0.05), Serum Creatinine p= 0.809 (p>0.05). The Telmisartan group experienced a decrease in average BUN of 4.74±5.16 mg/dl and serum creatinine of 0.33±0.20 mg/dl with Wilcoxon BUN test results p=0.000 (p<0.05), Serum Creatinine p=0.000 (p<0.05). In contrast, in the valsartan group, there was no change. So, it can be said that telmisartan has the highest effectiveness in kidney function (BUN and Serum Creatinine).